An Academic Library's Self-Study in Ethics: A Library-Wide Investigation of Ethical Practice. Issue 8 (17th November 2018) - Senior, Heidi; Scott, Jane
Abstract: In the fall of 2017, the Clark Library at the University of Portland undertook an investigation of ethics in academic libraries to understand ethical practices in the library's day-to-day work. The self-study was a year-long, library-wide project with directed activities within small groups, individually assigned readings and responses, and discussions at all-staff meetings. The project culminated in three specific deliverables: an annotated bibliography focused on ethical issues by functional area, a Clark Library Statement of Ethics, and a Statement of Ethical Information Use for inclusion in University syllabi.